2008
DOI: 10.2202/1556-3758.1470
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Tomato Concentrate

Abstract: Rheological properties of tomato concentrate were evaluated using a wide-gap rotational viscometer (Brookfield Engineering Laboratories: Model LVDV-II) at different temperatures of 20, 30, 40, 50, and 60oC, at concentration of 18, 12.18 and 8.04 % total solids, and at appropriate shear rate(1-100 RPM). The power law model was fitted to the experimental results. The values of flow behaviour index (n) were found less than unity (0.23 to 0.82) at all the temperature and the concentration indicating shear-thinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 7 publications
5
17
0
3
Order By: Relevance
“…This result suggests the existence of a shear rate limit, surpassing this limit, and shear stress values are only influenced by temperature modifications. The existence of a shear rate limit is an important result to be used in industrial equipment design (eg agitator, heat exchanger), and designing of vinasse transport and pump capacity (Dak et al, 2008a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests the existence of a shear rate limit, surpassing this limit, and shear stress values are only influenced by temperature modifications. The existence of a shear rate limit is an important result to be used in industrial equipment design (eg agitator, heat exchanger), and designing of vinasse transport and pump capacity (Dak et al, 2008a).…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of rheological properties of vinasses is very important, because it can be used for different engineering applications such as equipment design, designing of transport system, pump capacity design, and power requirements for mixing (Dak et al, 2008a). Shear-thinning properties of biological systems are frequently characterized by means of shear stress vs. shear rate rheological tests, which are used to characterize rheological parameters such as yield stress (t o ), consistency coefficient (K), and flow behaviour index (n) (Chaves et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that rheological properties of fruit concentrate depend greatly on the method of concentration of juice/pulp (Dak et al 2008;Sabanis et al 2008;Schlüter et al 2009). In this respect, it has been reported that the apparent viscosity of tomato purées prepared from hot break extracted juice by evaporation was much higher than that made by centrifuging out the insoluble solids, concentrating the serum, and then reconstituting (Harper and El Sahrigi 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados son consistentes con estudios reportados para otras frutas (tomate, piña, naranja y mango variedad Chausa) [19,[21][22][23]. El efecto combinado de la temperatura y concentración sobre el índice de consistencia de la pulpa de mango fue predicho por las Ecuaciones 6 y 7, cuyos parámetros se muestran en la Tabla 5.…”
Section: Concentraciónunclassified